2020
DOI: 10.1017/s0959270919000492
|View full text |Cite
|
Sign up to set email alerts
|

Fishery bycatch is among the most important threats to the European population of Greater ScaupAythya marila

Abstract: SummaryFor Greater Scaup Aythya marila, classified as ‘Vulnerable’ on the European Red List of Birds, the south-western Baltic Sea is one of the most important wintering sites in Europe. In this area, a large concentration of gillnet fishery temporally overlaps periods of the most abundant occurrence of foraging diving birds. The aim of the article is to show how bycatch can impact the population of a diving duck. To assess this, we calculate the Potential Biological Removal (PBR) for the studied Greater Scaup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We suspect that this may be partly the result of the significant decrease in the Scaup bycatch in the Netherlands 29 – 31 . The added mortality from fisheries bycatch represents one of the most important threats to the relatively long-lived Scaup 32 . Evidence showed that drowning mortality was extremely high between 1985 and 1994, when an estimated average of 17,672 birds died annually in fishing gear (6% of the total population of the time), but this has declined since the 2000s 32 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We suspect that this may be partly the result of the significant decrease in the Scaup bycatch in the Netherlands 29 – 31 . The added mortality from fisheries bycatch represents one of the most important threats to the relatively long-lived Scaup 32 . Evidence showed that drowning mortality was extremely high between 1985 and 1994, when an estimated average of 17,672 birds died annually in fishing gear (6% of the total population of the time), but this has declined since the 2000s 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The added mortality from fisheries bycatch represents one of the most important threats to the relatively long-lived Scaup 32 . Evidence showed that drowning mortality was extremely high between 1985 and 1994, when an estimated average of 17,672 birds died annually in fishing gear (6% of the total population of the time), but this has declined since the 2000s 32 . Of all Scaup from this flyway population that drowned in fishing nets in years 1978–1990, up to 65% died at the most important wintering site at the time—the Dutch IJsselmeer 32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations